Sanguínea by Gabriela Ponce or the Laughter of the Flesh - Bustamante, Mateo (2022)
In light of Rosi Braidotti’s nomadism and the grotesque studied by Bakhtin, the aim is to open a way to affirmatively think the body in literature. After analyzing the myths of descent through Ricoeur’s anthropology, the images of the hollow in Gabriela Ponce’s Sanguínea (2019) are observed in order to propose this as a figuration of the body, that is, the flesh as hollow which ungrounds normative discourses of the body. Through this figuration, a connection is proposed between the writing of the body and the development of the Renaissance grotesque. In this connection we find the necessary laughter to write about the flesh, a destabilizing laughter of the reign of the Subject as Selfhood (universal, masculine, white, heterosexual, rational).